2011
DOI: 10.1186/1471-2229-11-78
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anther transcriptomes to identify genes contributing to meiosis and male gametophyte development in rice

Abstract: BackgroundIn flowering plants, the anther is the site of male gametophyte development. Two major events in the development of the male germline are meiosis and the asymmetric division in the male gametophyte that gives rise to the vegetative and generative cells, and the following mitotic division in the generative cell that produces two sperm cells. Anther transcriptomes have been analyzed in many plant species at progressive stages of development by using microarray and sequence-by synthesis-technologies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
156
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(158 citation statements)
references
References 67 publications
(98 reference statements)
2
156
0
Order By: Relevance
“…Transcriptomic studies have been conducted in pollen, sperm, and anthers in diverse plant species, including Arabidopsis, rice, B. rapa, maize, and cotton (Gossypium hirsutum; Honys and Twell, 2004;Ma et al, 2007Ma et al, , 2008Ma et al, , 2012Chen et al, 2010;Fujita et al, 2010;Deveshwar et al, 2011;Yang et al, 2011;Dong et al, 2013;Wuest et al, 2013). While some studies were focused on tapetum and male gametophytes, others compared anthers of male sterile mutants with anthers of the wild type.…”
Section: Anthers Of Floral Stage 9 Transiently Express a Large Numbermentioning
confidence: 99%
“…Transcriptomic studies have been conducted in pollen, sperm, and anthers in diverse plant species, including Arabidopsis, rice, B. rapa, maize, and cotton (Gossypium hirsutum; Honys and Twell, 2004;Ma et al, 2007Ma et al, , 2008Ma et al, , 2012Chen et al, 2010;Fujita et al, 2010;Deveshwar et al, 2011;Yang et al, 2011;Dong et al, 2013;Wuest et al, 2013). While some studies were focused on tapetum and male gametophytes, others compared anthers of male sterile mutants with anthers of the wild type.…”
Section: Anthers Of Floral Stage 9 Transiently Express a Large Numbermentioning
confidence: 99%
“…A tissue-specific gene expresses in one particular tissue or cell type, whereas a housekeeping gene expresses in all tissues. Tissue-specific genes are believed to contribute mainly to the structural and functional diversification of different tissue types; thus, the functions of tissue-specific genes are often experimentally tested in the tissue in which the gene is expressed (Endo et al, 2008;Deveshwar et al, 2011;Xie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the DNA sequence of the RTS promoter isolated from the rice cultivar IR54 (Luo et al 2006) and IR64 (Deveshwar et al 2011) showed the insertion of a 44 bp stretch (at -1005 to -962 position) apart from 3 substitutions and 3 single base insertions. The promoter also carried an additional 264 bp at its 5' end.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may have led to the loss of tight regulation at the RTS promoter making the promoter leaky. Further, in the study by Deveshwar et al (2011), the activity of the gene was mainly studied by comparative analysis of the transcriptome and in situ hybridization studies. Strategies like comparative analysis of transcriptome and in situ hybridization, analyses activity of the promoter at its original genomic location, whereas studies done by developing transgenics, analyses activity of promoters at ectopic genomic locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation